Multi-terminal Experimental System Based on Wireless Local Area Network. (May 2020) - Fan, Kaigang; Chen, Xin; Zhao, Biao; Wang, Jiale; Cui, Wenbin; Ding, Junliang; Hu, Tao
Abstract: Aiming at the problems of single experimental data display, difficult data recording, poor human-computer interaction and low security for an experimental system, a multi-terminal experimental system based on Android operating system and wireless local area network was designed. Based on the Android operating system and wireless LAN, the system combines MySQL database, Web server, and LabVIEW software, and adopts modular design, realizes real-time collection and recording of experimental data during the experiment, and multi-parameters cross hardware display, good human-computer interface and remote status monitoring.